2019
DOI: 10.1002/cam4.2498
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reviews as a “lens of evidence”: Determinants of cost‐effectiveness of breast cancer screening

Abstract: Systematic reviews with economic components are important decision tools for stakeholders seeking to evaluate technologies, such as breast cancer screening (BCS) programs. This overview of systematic reviews explores the determinants of the cost‐effectiveness of BCS and assesses the quality of secondary evidence. The search identified 30 systematic reviews that reported on the determinants of the cost‐effectiveness of BCS, including the costs of breast cancer and BCS. While the quality of the reviews varied wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…When a comparison was made between biennial screening and annual or triennial screening, a biennial interval was found to be more cost-effective than the other screening interval strategies. This is in line with the conclusion of the review of systematic reviews by Mandrik et al [18] as well as the WHO recommendation of a screening interval of two years among women aged 50-69 years in well-resourced settings or limited resource settings with relatively strong health systems [1]. This recommendation was based on modelling studies and further analysis of trials showed that screening every two years seems to provide the best trade-off between benefits (mortality reduction) and harms (overdiagnosis or overtreatment).…”
Section: Study Findings and Implicationssupporting
confidence: 93%
“…When a comparison was made between biennial screening and annual or triennial screening, a biennial interval was found to be more cost-effective than the other screening interval strategies. This is in line with the conclusion of the review of systematic reviews by Mandrik et al [18] as well as the WHO recommendation of a screening interval of two years among women aged 50-69 years in well-resourced settings or limited resource settings with relatively strong health systems [1]. This recommendation was based on modelling studies and further analysis of trials showed that screening every two years seems to provide the best trade-off between benefits (mortality reduction) and harms (overdiagnosis or overtreatment).…”
Section: Study Findings and Implicationssupporting
confidence: 93%
“…Since implementation of BCS programs has already stimulated multiple discussions about their benefit/harm ratio and cost-effectiveness, 47 , 48 understanding how much support these programs gain from various groups, such as the medical community and the women themselves, can be an important parameter defining the programs’ priority on the political agenda. This is especially crucial for countries considering implementation of a population-wide screening program, re-assessing continuation of the existing program, or evaluating screening extension to other age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound and mammogram are established, cheap breast imaging methods. 66,67 We found that the pooled average sensitivity for the detection of breast cancer in patients with PND was 50% for ultrasound but only 22% for mammogram. Pooled specificity was 69% for ultrasound but much was higher, at 93%, for mammogram.…”
Section: Discussionmentioning
confidence: 90%